Peran Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Kepulauan Riau dalam Melaksanakan Fungsi Pengawasan Terhadap Perkembangan Perekonomian Pasca Pandemi Covid-19 di Kota Tanjungpinang - Wahyu Surya Wardana; Surya Surya; Titus Prastyo (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2022)
COVID-19 hit all lines of society wich made the economy falter especialy in Tanjungpinang City which was blocked by a little economic development due to COVID-19. This journal article will analyze and pay attancion to supervisory function of the Provincial Legislatives Council (DPRD) of the Riau Archipelago in accordance with Regulations No. 23 of 2014 concerning Regional Government whether it has an impact on economic development in Tanjungpinang City after COVID-19. The research method used is qualitative with descriptive qualitative research, the data source is obtained form primary data, nemely the results of interviews adn secondary data through the study of decisions, regulation and other important documents. This journal article conveys that the supervisory function of the Provincial Legislatives Council (DPRD) of the Riau Archipelago is very necessary to control economic development in Tanjungpinang City.